Location of fault in a hybrid power system using impedance based method - K. Panigrahi, Basanta; Pattanayak, Ruturaj; Parija, Bhagyashree; Panda, Chandini (International Journal of Engineering and Technology, 2018)
Fault analysis is a major and complex task for the power system engineers. It requires models, which determine the distance of the fault in the transmission line. By the use of mathematical models, we determine the behavior of faults and their locations, which help in preventing the transmission lines from heavy damage. Determining the fault location and their distance to buses is the sole objective of this paper. The method used for the fault location detection is impedance-based technique. For analysis, various faults at various locations of the system were modeled and simulated using MATLAB/SIMULINK. The results and applications are stated in this paper and it is found that this method is easier and most widely used.Â Â